Conservative surgery for laryngeal chondrosarcoma: a review of the most recently proposed approaches. Issue 2 (April 2017) - Piazza, Cesare; Paderno, Alberto; Nicolai, Piero
Abstract : Purpose of review: The aim of this study was to describe the most recent technical nuances for resection and reconstruction of Grade 1 and 2 laryngeal chondrosarcomas, with a special emphasis on those located at the level of the cricoid plate, which is the site of origin of the vast majority of these rare tumours. Recent findings: Even though inherently based on retrospective small clinical series or anecdotal case reports, a number of studies have been recently published focusing on conservative transoral and open-neck surgical procedures aimed at an oncologically sound removal of the tumour together with organ and function preservation. The open-neck conservative approaches herein reported can be roughly distinguished in those achieving a primary airway reconstruction by a tracheo-hyoido-epiglottopexy or an end-to-end crico-tracheal, thyro-crico-tracheal or thyro-tracheal anastomosis, and those requiring a single or double-staged transposition of different microvascular flaps, with or without cartilaginous graft insertion, to reconstruct a subtotal/total cricoidectomy and obtain a rigid and stable subglottic airway. Summary: No meaningful comparison in terms of oncologic and functional outcomes is still possible among the currently available conservative surgical strategies, due to the rarity of laryngeal chondrosarcomas and the heterogeneity of treatments proposed in the literature. However, a reasonable algorithm to approach this difficult clinical entity according to its site of origin and extent of cricoid circumference involved is herein presented.